Motivations and communication practices of scientists working at Portuguese universities - Entradas, M.; Sousa, I.C.; Yan, F. (EAAST/4S International Conference, 16-19 July, Amsterdam, 2024)
Science communication is now recognized as a responsibility of scientists. We see a growing demand and incentives for scientists and scientific institutions to communicate with external audiences and be active in public debates and science and technology policies. In recent decades, studies have emerged in several countries on the public communication practices of scientists, barriers and incentives for a scientists’ activity to address non-specialists, as well as their perceptions of the public. In Portugal, however, the topic is still lacking research. In this study with researchers working in Portuguese institutions (N=1500), in all areas of knowledge and career stages, we explore researchers' practices and perceptions about their role in science communication, as well as their practices and expectations about public involvement in science. We identify researchers' science communication activities, in traditional and new media, the audiences they target, and with what objectives. At the same time, we seek to explore how researchers' involvement in these actions relate to their conceptions of research integrity by measuring their research integrity practices and views. This study provides clues that could help scientific institutions and science communicators to support communication activities and scientists in their institutions.